ANALISIS IMPLEMENTASI STRATEGI DIGITAL MARKETING PADA SOSIAL MEDIA SEBAGAI SARANA PROMOSI BISNIS - Septyaningtyas, Rizmalia Nanda; Nugroho, Dian Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The current development of information technology, especially social media, offers benefits for business people to improve their marketing. The craft business in Indonesia is one of the creative industry sectors that is in great demand by business people because of its broad target market and increasing market demand. Gift box is an art and craft designed to give gifts to others by giving an interesting and unique impression. In the current era of globalization where gift box sales promotion can be done through social media. One of the social media that is currently trending among millennial youth is TikTok. This research was conducted to create a digital marketing strategy for the TikTok application to increase sales of the gift box aesthegift business. This research is a qualitative descriptive study using data collection methods, which use interviews/documentation and literature studies to obtain information and data. The purpose of this research is to find out how the strategy for creating digital marketing content on the TikTok application is right for increasing sales in the gift box aesthegift business.